2019
DOI: 10.1007/s00401-019-01961-w
|View full text |Cite
|
Sign up to set email alerts
|

Wide distribution of alpha-synuclein oligomers in multiple system atrophy brain detected by proximity ligation

Abstract: Multiple system atrophy (MSA) is a fatal adult-onset neurodegenerative disease that is characterized by varying degrees of cerebellar dysfunction and Parkinsonism. The neuropathological hallmark of MSA is alpha-synuclein (AS)-positive glial cytoplasmic inclusions (GCIs). Although severe neuronal loss (NL) is also observed in MSA, neuronal inclusions (NIs) are rare compared to GCIs, such that the pathological mechanism of NL in MSA is unclear. GCIs and NIs are late-stage pathology features relative to AS oligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 43 publications
5
57
0
Order By: Relevance
“…However, the concentration of CSF pS129-␣Syn oligomers was sharply elevated in the postmortem CSF samples of MSA patients compared to all other clinical groups [104]. Moreover, recent studies described that o-␣Syn was abundantly distributed in neurons and oligodendrocytes in MSA brain tissues using homotypic proximity ligation assay detection [105].…”
Section: Endogenous Oligomeric αSyn Assemblies In Neurodegenerative Dmentioning
confidence: 90%
“…However, the concentration of CSF pS129-␣Syn oligomers was sharply elevated in the postmortem CSF samples of MSA patients compared to all other clinical groups [104]. Moreover, recent studies described that o-␣Syn was abundantly distributed in neurons and oligodendrocytes in MSA brain tissues using homotypic proximity ligation assay detection [105].…”
Section: Endogenous Oligomeric αSyn Assemblies In Neurodegenerative Dmentioning
confidence: 90%
“…95 However, it was most recently reported that also neurons in MSA show α-syn oligomers depositions. 96 A recent study showed that α-syn filaments differ in DLB and MSA. 97 PD and DLB are usually distinguished based on the symptoms, with DLB being the second most common type of dementia.…”
Section: Synapse and Neuronal Loss In Brain Disordersmentioning
confidence: 99%
“…This technique offers great sensitivity because powerful rolling circle amplification is used. It also offers great selectivity because dual target recognition is used . Here, we used antibodies generated against both the N and C terminal domains of C99 in cultured cells and found that we can distinguish C99 from Ab, full‐length APP, C83, and AICD.…”
Section: Introductionmentioning
confidence: 99%